Analisis Multi User Orthogonal Frequency Division Multiplexing (OFDM) Berbasis Perangkat Lunak - Widya Catur Kristanti Putri (Politeknik Negeri Malang, 2016)
The application of OFDM technology is still not fully implemented in the Telecommunication Study Program at State Polytechnic of Malang. This is because the application of this technology is applied to hardware. However, this can be overcome by simulating the OFDM technology through software. From the application of the system into the program by entering the predetermined parameters, the BER value can be compared to the predetermined parameters. Bit error that appears in the application of the OFDM Multi user system for bit error in BPSK Modulation with AWGN and Rayleigh Fading channels appears bit error respectively with an average of 9 bits and 14 bits at 11 dB SNR. Whereas in the QPSK modulation with AWGN and Rayleigh Fading channels, each bit error appears with an average of 13 bits and 18 bits on the SNR of 14 dB. Furthermore, in the calculation of bandwidth efficiency in the frequency allocation of 20 MHz for BPSK modulation, three values ??of bandwidth efficiency are obtained, among others, 1 bps / Hz in theory for practical, namely the code rate ½ is 0.3 bps / Hz and the code rate ¾ is 0.45 bps / Hz. While the QPSK modulation also obtained three values ??of bandwidth efficiency, namely, 2 bps / Hz in theory for practical, namely the code rate ½ is 0.6 bps / Hz and the code rate ¾ is 0.9 bps / Hz.